Weight gain and serum leptin levels in patients on lithium treatment - Atmaca, M; Kuloglu, M; Tezcan, E; Ustundag, B (Karger, 2002)
Weight gain is a frequent adverse effect associated with lithium use. Leptin is an adipocyte hormone, regulating food intake and energy balance providing the hypothalamus with information on the amount of body fat. Therefore, we planned to evaluate whether lithium administration was associated with weight gain, and leptin levels. The study consisted of 15 consecutive inpatients with bipolar I disorder according to DSM-III-R. The fasting serum leptin levels were measured. The patients were evaluted at baseline and at the eighth week according to the body mass index, weight, Young Mania Rating (YMRS) and Hamilton Depression Rating (HAM-D) scales, and serum leptin levels. With respect to the leptin levels, a significant difference was observed after lithium treatment. There was a significant positive correlation between the changes in leptin levels and the duration of illness. The change in total YMRS scores correlated with change in leptin levels and that in weight. In conclusion, our result suggest that leptin may be associated with lithium-induced weight gain. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: leptin; lithium; weight; serotonin